ANALISIS PENGARUH PENDEKATAN PERSONAL TENAGA PENJUAL, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN PELANGGAN (Jurnal Pilar Nusa Mandiri, 2014)
In a high level of a competitive environment, every business must maintain their customer. This study, therefore, intent to search several variables’ effect which is probably able to raise customer satisfaction. The study used several customers of  PT PENERBIT ERLANGGA  as a sample. Data analyze instrument used by the writer is SPSS 17. Data analyze result shows that the research model has well appropriateness and all hypothesis of the study are able to be evidenced. The summary said that personal approach of a salesperson, product quality and price are positively affected to customer satisfaction. Based on the result of  the  study,  managerial  implication  given  to the  company  is  suggestion  or  input  to the management of  PT PENERBIT ERLANGGA to give more concern at the price, as it is the most dominant factor effected to customer satisfaction